PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN PERTUMBUHAN ASET TERHADAP PROFITABILITAS PERUSAHAAN (PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2015) - admin admin; LALU RIZAL IHWANDI (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2019)
The purpose of this study to test the effect of disclosure of corporate social responsibility(CSR) and asset growth to profitability. This study was conducted using a sample of 10companies listed on the stock exchange in 2011-2015. Methods of sample selection usingpurposive sampling and analysis model used is multiple linear regression.The result of thisstudy indicate that the disclosure of corporate social responsibility (CSR) positive andsignificant impact on profitability. It can be seen from the positive coefficient of 0,178, with asignificance of 0,032 < than the significance level of 0,05. Asset growth and no significantpositive effect on profitability. It can be seen from the positive coefficient of 0,074, with asignificance of 0,249 > than the significance level 0,05. While the disclosure of corporatesocial responsibility (CSR) and the asset growth influence simultaneously (together) toprofitability. This is demonstrated by the significant F of 0,044 < of at significance level of 0,05.